Studies on microfungal diversity of King George Island and analysis of hydrolase enzymes of selected species / Abiramy Krishnan @ Ramasamy - Krishnan @ Ramasamy, Abiramy (2011)
Antarctica hosts a wide range of psychrophilic and psychrotolerant microbes, and thus is a prime choice for studies of the production of cold-functioning enzymes and other metabolites. However, the occurrence and importance of investment in such activities has received relatively limited attention in studies of Antarctic soil microbiota. In order to ex-amine extracellular enzyme production in this chronically low temperature environment, fungi were isolated from ornithogenic, pristine and human-impacted soils collected from the Fildes Peninsula, King George Island, Antarctica during the austral summer in February 2007. Forty-one fungal taxa were isolated from soil samples, from which 28 isolates of psychrophilic and psychrotolerant taxa were obtained. These were screened at a culture temperature of 4°C for production and activity of extracellular hydrolase enzymes (amylase, cellulase, protease), using R2A agar plates supplemented with either: (a) starch for amylase activity, (b) carboxymethyl cellulose and trypan blue for cellulase activity, or (c) skim milk for protease activity. Sixteen isolates showed activity for amylase, 23 for cellulase and 21 for protease. One isolate showed significant activity across all three enzyme types and a further 10 isolates showed significant activity for at least two of the enzymes. The screen-ing test was followed with enzyme quantification for amylase and cellulase. Geomyces pannorum and Mrakia frigida were identified to posses significant enzyme activity for both enzymes. There was no clear association between the fungal taxa isolated and the type of source soil, or in the balance of production of different extracellular enzymes between the different soil habitats sampled. Investment in extracellular enzyme production is clearly an important element of the survival strategy of these fungi in maritime Antarctic soils.